Development of a green and efficient methodology for the heterocyclic aromatic amine determination in biomass samples generated from cigarette combustion and tobacco - Canales, Romina (2020)
A green methodology was developed for the analysis of ten heterocyclic aromatic amines (HAAs) in biomass samples from cigarette combustion such as mainstream smoke, paper ashes, as well as tobacco and paper wraps. The cellulose filter used for sample collection was also evaluated. This strategy was based on ultrasound-assisted extraction (UAE) associated with a solid-phase extraction procedure employing multi-walled carbon nanotubes (MWCNTs-SPE) as a cleanup step followed by ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Under optimal experimental conditions, the linearity of the method was in the range from 0.08 to 160 ng cig-1, with correlation coefficients (R2) higher than 0.991. The limits of detection resulted to be between 0.03 and 0.63 ng cig-1. Concentrations of the HAAs in the mainstream smoke were from 5.7 to 145.2 ng cig-1 and in paper ashes from 0.1 to 0.6 ng cig -1, while in tobacco were between 1.0 and 38.5 ng cig-1. Meanwhile, no HAA contribution was observed in the case of paper wraps and the filter used for sample collection. The knowledge of the presence and the concentration levels of the selected HAAs in each cigarette’s physical component after its combustion is essential to understand the formation processes and contribution during cigarette burning. Besides, this is the first report about the presence of some HAAs in the proposed samples. Finally, a comparative study was employed to classify the sustainability of several recent approaches for HAA extraction from cigarette combustion samples using Green Certificate as a metric tool.